Caffeine in Chocolates a Hazardous Sign to Children?óÔé¼Ôäós Health - Kasimala, Bikshal Babu (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTCaffeine is an alkaloid isolated from plant species. Caffeine is most commonly used to improve mental alertness. It is also used with painkillers for simple headaches and preventing and treating headaches after epidural anesthesia. 250 milligrams of caffeine per day chocolates is considered an average. For children?óÔé¼Ôäós the dosage will be very low. It is used as an ingredient in the manufacture of many numbers of chocolates. Children?óÔé¼Ôäós are very much found off chocolates. But chocolates contain high amount of caffeine content relative to their daily intake of tolerable caffeine dosage. The dosage of the caffeine increase causes hazardous health effects to the children?óÔé¼Ôäós. The present study deals with the amount of caffeine present in different chocolates available in local market.